The Acqualadroni Ram Recovered Near the Strait of Messina, Sicily: dimensions, timbers, iconography and historical context. (4th December 2012) - Buccellato, Cecilia A.; Tusa, Sebastiano
<x xml:space="preserve">Abstract</x> Within the framework of the activities of the Soprintendenza del Mare of Sicily, a bronze ram was recovered just north of the Straits of Messina, in the area of Acqualadroni. This paper discusses technical and iconographic features of the ram and compares them with others found in Sicily, Piraeus, Tuscany and Athlit. The study shows the Acqualadroni Ram has more analogies with the latter, although it also has unique features. Radiocarbon dating suggests that the ram was used on a warship dating from the mid‐2nd century BC. It is therefore possible that the Acqualadroni Ram was lost during the Naulochus battle (36 BC) or during the Civil Wars that gave rise to the rule of Octavian.